Hubungan Pengetahuan dan Perilaku Ibu dalam Pemberian Makanan Pendamping ASI pada Balita Stunting di Desa Gerbosari dan Sidoarjo, Samigaluh, Kulon Progo - Siti Maryati; Prita Yunitasari; Budi Punjastuti (Jurnal Indonesia Sehat, 2022)
Background Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. The case of stunting toddlers in 2020 in Kulonprogo occupies the 3rd position in the DIY Province with a prevalence of 12.57% from 2,712 toddlers, which means that there are 341 toddlers experiencing stunting in Kulonprogo. The most cases were in Samigaluh, Girimulyo and Kalibawang above 20%. The purpose of the study was to determine the relationship between knowledge and mother's behavior in providing complementary feeding (MP-ASI) to stunted toddlers in Gerbosari Village and Sidoarjo Samigaluh Village, Kulonprogo.The research method used was observational analytic with a cross sectional approach. The population in the study were all mothers who had stunted children under five in Gerbosari Village and Sidoarjo Samigaluh Village, Kulonprogo. The sampling technique in this study was to use Total Sampling. The number of samples used was 61 people. The results showed that the characteristics of the respondents were mostly between the reproductive age of 20-35 years as much as 73.77%, the average high school graduate education was 52.46%, and most were not working as much as 86.89%, the average obstetric history of the mother had 2 children. as much as 49.18%. The level of knowledge of mothers about MP-ASI on average is categorized as sufficient as much as 55.7%, while the behavior of mothers in giving MP-ASI mostly has positive behavior as much as 85.2%. complementary feeding indicated by a sig value of 0.088 (> 0.05).The conclusion is that there is no relationship between the mother's level of knowledge about giving complementary foods and the behavior of mothers in giving complementary foods.